The Effectiveness of Mozart Music on the Level of Women's Pain in the First Stage Labour - Karlina Karlina; Abela Mayunita (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Pain is something that is certain in every delivery, so complementary care to reduce pain intensity is very important to consider. Mozart's music has been studied to activate physiological pathways that can modulate the body's response. The purpose of this study was to analyze the effectiveness of Mozart's music therapy in reducing the intensity of labor pain. This study was a quasi-experimental design. This research was conducted at the Independent Practice of Midwives Bd Hj. Nining Mutbaiyyah, S.ST Pamarayan, Serang – Banten in May – June 2023. The sample in this study was 30 respondents divided into 15 intervention groups and 15 control groups. Samples were selected by purposive sampling techniques. The intervention provided was the playback of Mozart's music with the title K 448 Mozart every 30 minutes. Analysis using the Mann Whitney U test . There was a difference in the average degree of pain between the control group and the intervention group (6.4 vs 4.5) In addition, the results of the Mann Whitney test also showed a p-value of 0.000 < 0.05 which concluded that there was an influence between the administration of Mozart music intervention in reducing pain in maternity mothers and was statistically significant.